Dialektologi bahasa Bugis di Sabah (Jurnal Bahasa, 2006)
This data was collected in Tawau district of Sabah due to the fact that the Bugis community who migrated to Sabah from South Sulawesi lsland had settled in the district a long time ago. Today, the Bugis language is still used by the Bugis community in that particular district. The Bugis people rise from a civilized race. They have their own writing script which they named Lontara. The Bugis people of Tawau district relate the birth of their writing script with that of I La Galigo a poem inspired by the Bugis legend. However; in reality the Bugis Ianguage is determined by its surrounding sound features. It is proven by the existence of allomorph. The main word class in the Bugis Ianguage consists of noun, verb, and adjective, which is identical with that of a Malay language.